2020
DOI: 10.1111/gcb.15084
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting acclimation responses to elevated CO2 and warming between an evergreen and a deciduous boreal conifer

Abstract: Rising atmospheric carbon dioxide (CO 2 ) concentrations may warm northern latitudes up to 8°C by the end of the century. Boreal forests play a large role in the global carbon cycle, and the responses of northern trees to climate change will thus impact the trajectory of future CO 2 increases. We grew two North American boreal tree species at a range of future climate conditions to assess how growth and carbon fluxes were altered by high CO 2 and warming. Black spruce (Picea mariana, an evergreen conifer) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 130 publications
(331 reference statements)
9
83
0
Order By: Relevance
“…Peat drying and increases in nutrients could increase tree recruitment and growth ( 29 ), and we see some evidence of this in the increased larch fine-root biomass ( SI Appendix , Fig. S3 ) and aboveground growth ( 24 ).…”
Section: Strong Increases In Shrub Fine-root Growthmentioning
confidence: 88%
See 1 more Smart Citation
“…Peat drying and increases in nutrients could increase tree recruitment and growth ( 29 ), and we see some evidence of this in the increased larch fine-root biomass ( SI Appendix , Fig. S3 ) and aboveground growth ( 24 ).…”
Section: Strong Increases In Shrub Fine-root Growthmentioning
confidence: 88%
“…Shrubs may be taking a "do-it-yourself" approach by increasing the length production of new roots for foraging, while larch may be mainly "outsourcing" resource acquisition by investing in mycorrhizal fungal partners (22); both strategies have implications for total belowground C input, decomposition rates (23), and ultimately, peatland C storage. Lastly, the tree fine-root response may be mirroring aboveground C gain; parallel investigations have found that seedlings of the two tree species differ in their aboveground responses to warming (positive for larch, negative for spruce) (24). Investigations of PFT-specific root-fungal interactions and aboveground-belowground linkages in the bog are underway, but for the remainder of the manuscript, we focus on the shrub fine root-length response given that it was the strongest and earliest response and has implications for peatland C function through negative effects of shrubs on the growth of keystone Sphagnum mosses.…”
Section: Fine Roots Increase With Warming But Due To Dryingmentioning
confidence: 99%
“…The observed shift in T optA , 0.6°C per 1°C warming in AO 3 , is consistent with previously reported values that typically are in the range of 0.3–0.5°C per °C change in growth temperature (Battaglia et al, 1996; Berry & Björkman, 1980). However, even greater T optA shifts have been reported (e.g., Dusenge et al, 2020; Sendall et al, 2015), suggesting that considerable differences exist in the physiological capacities for photosynthetic thermal acclimation among trees species. In addition, variations in the degree and duration of temperature treatments and in the surrounding environmental factors likely explain some of the reported differences.…”
Section: Discussionmentioning
confidence: 99%
“…Much work has recently been carried out on determining the impact of growth temperature on T optA (e.g., Aspinwall et al, 2016; Crous et al, 2018; Kumarathunge et al, 2019; Scafaro et al, 2017; Slot & Winter, 2017b). Other environmental factors, such as atmospheric CO 2 concentrations (e.g., Crous et al, 2013; Dusenge et al, 2020; Ghannoum, Phillips, Sears, et al, 2010; Kurepin et al, 2018), light availability (Niinemets et al, 1999), and water limitation (Kumarathunge et al, 2020), are also known to both independently affect the T optA and to modify its acclimation response to warming. However, while tropospheric ozone (O 3 ) is recognized as an important regional air pollutant with strong effects on plant gas exchange (e.g., Ainsworth et al, 2012; Dai et al, 2017; Feng et al, 2016), its impact on photosynthetic thermal acclimation potential is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Observed differences in mycelial morphology between the two ends of the temperature gradient at SPRUCE may be related to ECM host performance (Fernandez et al, 2017). At SPRUCE, multiple data streams indicate that L. laricina individuals may be better acclimating to warming than P. mariana individuals (Dusenge et al, 2020;Peters et al, unpublished data;Peters (JP) Fernandez et al (2019). Accordingly, ECM rhizomorph formers may recycle mycelium to minimize nitrogen immobilization in their biomass, thereby providing the nitrogen surplus to their plant hosts (Clemmensen et al, 2015).…”
Section: Rhizomorph Abundancementioning
confidence: 99%